Nawat Phusa: Promoting innovation of natural banana fibers into product design to enhance cultural creative economy products through performing arts approach - Rittibul, Pravit; Boontonglek, Manoch; Ngerndang, Artitaya; Orachun, Riswan; Nasom, Chananchida (Edelweiss Applied Science and Technology, 2025)
This study investigates the origin and conceptual development of innovative banana fiber fabrics for application in the performing arts. Utilizing qualitative and creative research methodologies, data were collected through academic document analysis, interviews, multimedia sources, field surveys, and the researcher’s experiential insights. The data were systematically analyzed and presented in both academic and performing arts frameworks. The findings indicate that banana fiber fabric represents a significant form of cultural capital in Pathum Thani Province, serving as the basis for developing textile innovations derived from banana fibers. This process integrates local wisdom grounded in the philosophy of a sufficiency economy. The study further identifies eight key elements of dramatic arts essential for integrating banana fiber fabrics into the performing arts: (1) performance design, (2) performer selection, (3) choreography design, (4) prop design, (5) sound and music composition, (6) costume design, (7) lighting design, and (8) performance space design. These elements were examined with respect to creativity, symbolism, and theoretical frameworks in dance, music, and visual arts.